Differences in Complication Rates Between Large Bore Needle and a Long Micropuncture Needle During Epicardial Access. (August 2015) - Gunda, Sampath; Reddy, Madhu; Pillarisetti, Jayasree; Atoui, Moustapha; Badhwar, Nitish; Swarup, Vijay; DiBiase, Luigi; Mohanty, Sanghamitra; Mohanty, Prashanth; Nagaraj, Hosakote; Ellis, Christopher; Rasekh, Abdi; et al.
<x xml:space="preserve">Abstract</x> Background— A dry epicardial access (EA) is increasingly used for advanced cardiovascular procedures. Conventionally used large bore needles (Tuohy or Pajunk needle; LBN) have been associated with low but definite incidence of major complications with EA. Use of micropuncture needle (MPN) may decrease the risk of complications. We intended to compare the outcomes of LBN with MPN for EA. Methods and Results— We report a multicenter observational study of consecutive patients who underwent EA for ventricular tachycardia ablation or Lariat procedure using the LBN or MPN. Oral anticoagulation was stopped before the procedure. Baseline characteristics and procedure-related complications were collected and compared. Of the 404 patients, LBN and MPN were used in 46% and 54% of patients, respectively. There was no significant difference in the incidence of inadvertent puncture of myocardium between LBN and MPN (7.6% versus 6.8%, P=0.76). However, there was a significantly higher rate of large pericardial effusions with LBN compared with MPN (8.1% versus 0.9%; P<0.001). The incidence of pleural effusions were not significantly different between both (1.6% versus 2.3%; P=0.64). LBN group had an increase in other complications compared with MPN (open heart surgery to repair cardiac laceration [6 versus 0], injury to liver [1 versus 0], coronaries [1 versus 0], and superior epigastric artery requiring surgical exploration [0 versus 1]). Conclusions— The use of MPN is associated with decreased incidence of major complications, and the need for surgical repair and routine use should be considered for EA.